O-100 Northern region health plan – New Zealand. (1st September 2015) - Manson, Leigh; Muir, Shona
Abstract : Background: Early in the development of ACP in New Zealand, the Northern Region, a collaborative of four District Health Boards (DHBs), formed to address issues that would be better dealt with regionally. ACP was identified as the area of focus under the Informed Patient Stream within the first Northern Region Health Plan. Aim: To increase the uptake of ACP by means of a regional approach to ACP, with pooling of limited resource and a focus on delivery of change. Methods: ACP programme objectives were agreed to by the DHB executive groups, and targets were set. Funding was pooled and a small central team was created, so the region was able to: support DHBs and other service providers to draft policies coordinate the development of resources for the healthcare workforce and to raise awareness of ACP in the general population allow for economies of scale for the printing and distribution of printed resources purchase training for healthcare providers in the DHB areas coordinate the training ensure that those trained were well supported to participate in ACP with patients. Results: Pooled resourcing and centralisation of skill ensured that the four DHBs surpassed their annual ACP targets. Discussion: ACP was not seen as a key priority for the districts until there was a regional target to achieve and central support to assist and guide their efforts. Conclusion: ACP would not have been as successful in the four DHBs if the Northern Regional Health Plan had not incorporated ACP as a key deliverable for the Informed Patient Stream.